2021
DOI: 10.1103/physreva.103.013721
|View full text |Cite
|
Sign up to set email alerts
|

Transverse optical binding for a dual dipolar dielectric nanoparticle dimer

Abstract: The physical origins of the transverse optical binding force and torque beyond the Rayleigh approximation have not been clearly expressed to date. Here, we present analytical expressions of the force and torque for a dual dipolar dielectric dimer illuminated by a plane wave propagating perpendicularly to the dimer axis. Using this analytical model, we explore the roles of the hybridized electric dipolar, magnetic dipolar, and electric-magnetic dipolar coupling interactions in the total force and torque on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Consequently, FRay grossly underestimates the LOBF and even departs from Fe where the magnetic and electric-magnetic coupling effects are considered. This is similar to the TOBF for dielectric particles [30]. On the other hand, we focus on the stable and unstable equilibrium positions of FRay and LOBF (also termed the stable and unstable equilibrium separations of the two particles).…”
Section: A Polystyrene Homodimermentioning
confidence: 85%
See 3 more Smart Citations
“…Consequently, FRay grossly underestimates the LOBF and even departs from Fe where the magnetic and electric-magnetic coupling effects are considered. This is similar to the TOBF for dielectric particles [30]. On the other hand, we focus on the stable and unstable equilibrium positions of FRay and LOBF (also termed the stable and unstable equilibrium separations of the two particles).…”
Section: A Polystyrene Homodimermentioning
confidence: 85%
“…In the framework of the optical force on a single dielectric particle [28] and electromagnetic wave mutual scattering [29] (or see Appendices in Ref. [30]), the LOBF is analytically decomposed into the electric dipolar, magnetic dipolar, and electric-magnetic dipolar coupling components. In detail, the electric dipolar component of the LOBF on particle j (j=A or B) is expressed as…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The double-well potential can be used to study collective particle dynamics, e.g., optical binding 21 and forces between levitated particles. 210 Arita et al 211 demonstrated trapping and rotation of two microparticles in vacuum using an SLM-based approach, allowing individual control over the rotation direction and rate to each trap and the interparticle separation. By trapping and rotating two vaterite birefringent microparticles with circularly polarized light, they observed macroscopic Raman-like modulation of the incident light field at the sum and difference frequencies with respect to the individual rotation rates.…”
Section: Levitated Optomechanics With Structured Light Beamsmentioning
confidence: 99%